Issues and design approach for product oriented manufacturing systems - Alves, Anabela Carvalho (2010)
The Product Oriented Manufacturing (POM) concept here presented addresses competition in today’s changing global market of manufacturing companies. It is a challenge to the Function Oriented Manufacturing (FOM) concept supposedly adequate for dealing with demand changes and large product variety without needing reconfiguration. The POM concept evolves from the traditional cellular manufacturing, ultimately aiming at full system integration and coordination for completely processing a product, not parts of it, or a family of similar products, for efficient manufacturing and good customer service. In this respect it is customer order centred. For answering changing demand it draws upon system adaptation exploring several reconfiguration strategies. Due to POM complexity and design focus, a design methodology called GCD was developed and is here briefly described. The first phase, the Generic Design, is emphasized in relation to the others. It is mainly directed to analysing manufacturing companies’ demand market position and current manufacturing system in order to evaluate, at a generic level, the suitability of the POM concept for manufacturing. Further design phases explore alternatives of POM systems to reach a POMS suitable solution.